2020
DOI: 10.36899/japs.2021.1.0198
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Time Effect on Quantitativeandqualitative Parameters of Forage Maize

Abstract: Maize silage is source of palatable and high-energy forage for ruminants. Therefore, production of high quality forage maize represents an essential strategy for stable production of milk and meat on livestock farms. This study examined the effect of harvest date (early dent, at half milk line, at three quarters milk line and black layer) on the quantitative and qualitative parameters of whole maize plant under contrasting climatic conditions in the Srem -Serbia. A 2 × 4 factorial (two years and the four cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, ear development influenced the results, since although the R stage was the same in both years, ears included more DM in 2020 than in 2019. The CP content of the yield tends to decrease with ear development [56,57] since, during ear filling, the plant breaks down CP to provide N for carbon assimilation [56]. In Maaninka, the CP content was close to that observed in Helsinki in 2019 and was within the range of the previous Swedish studies [8,15].…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, ear development influenced the results, since although the R stage was the same in both years, ears included more DM in 2020 than in 2019. The CP content of the yield tends to decrease with ear development [56,57] since, during ear filling, the plant breaks down CP to provide N for carbon assimilation [56]. In Maaninka, the CP content was close to that observed in Helsinki in 2019 and was within the range of the previous Swedish studies [8,15].…”
Section: Discussionsupporting
confidence: 72%
“…Previously, in Sweden, Hetta et al (2012) observed that the DM yield was highest at the ear developmental stage of R5 when the DM content was 370 g kg -1 . Also, in Serbia, Mandić et al (2020) showed that DM yield increased until the DM content was 450 g kg -1 . Compared with those previous studies (Hetta et al 2012, Mandić et al 2020, the accumulation of DM yield ceased relatively early in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Also, in Serbia, Mandić et al (2020) showed that DM yield increased until the DM content was 450 g kg -1 . Compared with those previous studies (Hetta et al 2012, Mandić et al 2020, the accumulation of DM yield ceased relatively early in this study. The early cessation of DM yield increment was most likely related to leaf senescence and harvest losses.…”
Section: Discussionmentioning
confidence: 95%
“…When preparing corn silage, must be pay attention to the time of the beginning of the harvest and the corn cutting height (Mandić et al, 2020). A study by Bumb et al (2016), showed that the quality of forage and yield is significantly affected by the time of harvest.…”
Section: Introductionmentioning
confidence: 99%